1997
DOI: 10.1161/01.str.28.8.1550
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intensity of Rehabilitation After Stroke

Abstract: A small but statistically significant intensity-effect relationship in the rehabilitation of stroke patients was found. Insufficient contrast in the amount of rehabilitation between experimental and control conditions, organizational setting of rehabilitation management, lack of blinding procedures, and heterogeneity of patient characteristics were major confounding factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
280
2
17

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 526 publications
(318 citation statements)
references
References 30 publications
10
280
2
17
Order By: Relevance
“…The MIT-MANUS results showed that subacute patients who received robotic therapy in addition to their regular therapy improved more than patients who did not receive this added robot therapy. However, several meta-analyses have concluded that greater intensity of conventional therapy is also effective, resulting in decreased levels of impairment, disability, 17,18 and reduced mortality. 19 For robotic manipulation to gain clinical acceptance, it must first be shown that it offers advantages to conventional therapy or at least is no less effective than conventional therapy.…”
mentioning
confidence: 99%
“…The MIT-MANUS results showed that subacute patients who received robotic therapy in addition to their regular therapy improved more than patients who did not receive this added robot therapy. However, several meta-analyses have concluded that greater intensity of conventional therapy is also effective, resulting in decreased levels of impairment, disability, 17,18 and reduced mortality. 19 For robotic manipulation to gain clinical acceptance, it must first be shown that it offers advantages to conventional therapy or at least is no less effective than conventional therapy.…”
mentioning
confidence: 99%
“…In general, studies in humans have demonstrated that greater intensity of rehabilitation leads to better outcomes [95][96][97][98].…”
Section: Better Treatment Planmentioning
confidence: 99%
“…Practically, the large volume of literature supporting the effectiveness of increased intensity and duration of rehabilitation [89,[95][96][97] serves to highlight the importance of seeking potential alternatives to the traditional one-onone approach taken in stroke rehabilitation. Robots can deliver treatment with a therapy aide or technician supervising the operation of the device, thus allowing for a potential increase in the total dose of treatment received and optimizing use of the therapist's time.…”
Section: Rationale For Using Robots For Treatmentmentioning
confidence: 99%
“…Several studies prove that arm therapy has positive effects on the rehabilitation progress of stroke patients [1][2][3][4][5][6][7]. So, the interested in using the robotic device to help rehabilitation therapy is increasing.…”
Section: Introductionmentioning
confidence: 99%
“…And because the population of the stroke patient is increasing and the number of therapists is insufficient, affecting the quality of rehabilitation and daily care. Basic neurological research suggests that the intensive and task-specific movement training can improve muscle strength and motor recovery in stroke patient [1,2]. The conventional rehabilitation by the therapist has several limitations such as personnel shortage and fatigue of therapists.…”
Section: Introductionmentioning
confidence: 99%